Mapping molecules to structure: unveiling secrets of centriole and cilia assembly with near-atomic resolution - Jana, Swadhin Chandra (2014)
Centrioles are microtubule (MT)-based cylinders that form centrosomes and can be modified into basal bodies that template the axoneme, the ciliary MT skeleton. These MT-based structures are present in all branches of the eukaryotic tree of life, where they have important sensing, motility and cellular architecture-organizing functions. Moreover, they are altered in several human conditions and diseases, including sterility, ciliopathies and cancer. Although the ultrastructure of centrioles and derived organelles has been known for over 50 years, the molecular basis of their remarkably conserved properties, such as their 9-fold symmetry, has only now started to be unveiled. Recent advances in imaging, proteomics and crystallography, allowed the building of 3D models of centrioles and derived structures with unprecedented molecular details, leading to a much better understanding of their assembly and function. Here, we cover progress in this field, focusing on the mechanisms of centriole and cilia assembly.